2020
DOI: 10.1039/d0dt01024c
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of π-extended B ← N coordinated phenanthroimidazole dimers and their linear and nonlinear optical properties

Abstract: B ← N coordinated phenanthroimidazole dimers exhibit excellent fluorescence quantum yields in solution and conjugation length dependant two-photon-absorption properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

8
0

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 92 publications
1
9
0
Order By: Relevance
“…In all these compounds, the boron atom adopts a slightly distorted tetrahedral geometry and deviate from the five‐membered plane defined by C 2 N 2 B (boron atom, pyrazole two nitrogen atoms, and phenyl carbons directly attached to boron and nitrogen); the distance ranging from 0.0072 to 0.0667 Å (Table S2). The B−N and B−C distances are in the typical range (Table S1) and are consistent with values reported in the literature [7f–i] . The interplanar angle between the N‐phenyl (Plane A) and pyrazole is 13.09 ° (for 12 ), 11.037 ° (for 13 ), 5.851 ° & 1.492 ° (for 14 ), 7.52 ° (for 15 ), 9.959 ° (for 16 ), and 3.182 ° (for 17) which indicates pyrazole and N‐phenyl skeleton have slight distortion.…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…In all these compounds, the boron atom adopts a slightly distorted tetrahedral geometry and deviate from the five‐membered plane defined by C 2 N 2 B (boron atom, pyrazole two nitrogen atoms, and phenyl carbons directly attached to boron and nitrogen); the distance ranging from 0.0072 to 0.0667 Å (Table S2). The B−N and B−C distances are in the typical range (Table S1) and are consistent with values reported in the literature [7f–i] . The interplanar angle between the N‐phenyl (Plane A) and pyrazole is 13.09 ° (for 12 ), 11.037 ° (for 13 ), 5.851 ° & 1.492 ° (for 14 ), 7.52 ° (for 15 ), 9.959 ° (for 16 ), and 3.182 ° (for 17) which indicates pyrazole and N‐phenyl skeleton have slight distortion.…”
Section: Resultssupporting
confidence: 88%
“…Pyrazole based B−N coordinated dibromoborane compounds 11 a – 17 a were prepared from their corresponding pyrazole ligands through an electrophilic aromatic borylation reaction with BBr 3 under basic condition (i ‐Pr 2 NEt) [7f–i] . Without further purification, the pyrazole‐dibromoborane compounds ( 11 a – 17 a ) were treated with trimethylaluminum (AlMe 3 ) to afford the desired products 11 – 17 in moderate yields (Scheme 2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We recently reported tetra-coordinated boron-functionalized phenanthroimidazoles and studied their linear and nonlinear optical properties . We have now coupled this tetra-coordinated boron motif with a zinc­(II) salen and utilized the hybrid system for the chemical transformation of CO 2 and oxiranes to produce cyclic carbonates using visible light.…”
mentioning
confidence: 99%
“…13; 106-109). 119,120 Photophysical studies revealed that the phenanthroimidazole and triaryl pyrazole based dimers exhibited considerable red shift absorption over the monomeric borylated systems due to the increased conjugation length. Fluorescence experiments of phenanthroimidazole dimers showed intense emission maxima ranging from 418 nm to 480 nm with excellent quantum yields up to 99% in the solution state and moderate quantum yields in the solid state.…”
Section: Perspective Dalton Transactionsmentioning
confidence: 99%